Treatment Methods for Knee Osteoarthritis - A Literature Review - Oskar Tudaj; Krzysztof Sajewicz; Aleksandra Mazur; Mikołaj Kaczmarek; Wiktoria Grochowska; Adrianna Dylik; Julia Kalisiak; Wiktoria Kalas; Paulina Strzałkowska; Julia Dulęba (Quality in Sport, 2025)
Introduction And objective: